2021
DOI: 10.3389/fonc.2021.645757
|View full text |Cite
|
Sign up to set email alerts
|

NSG Mice Facilitate ex vivo Characterization of Ewing Sarcoma Lung Metastasis Using the PuMA Model

Abstract: Ewing sarcoma (EwS) is a highly malignant bone and soft tissue tumor primarily affecting children and young adults. While most patients initially respond well to conventional front-line therapy, frequent metastasis results in poor 5-year overall survival rates for this disease. Accordingly, there is a critical need to develop better models to understand EwS metastasis. We and others previously used the ex vivo pulmonary metastasis assay (PuMA) to study lung metastasis in solid tumors including osteosarcoma (OS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…A similar study by Varano et al [ 13 ] investigating the effect of intraperitoneal AZ on retinal ischemia in a male Wistar rat model found that it had a neuroprotective effect. Ours is the first study, to the best of our knowledge, to examine an ONC model in NSG mice, which are usually used to investigate cancer, not ischemic or inflammatory diseases [ 27 , 28 , 29 ]. We propose that NSG mice might also serve for the study of the latter conditions, as a neuroinflammatory response is relevant in a wide spectrum of ocular diseases, including diabetic retinopathy [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…A similar study by Varano et al [ 13 ] investigating the effect of intraperitoneal AZ on retinal ischemia in a male Wistar rat model found that it had a neuroprotective effect. Ours is the first study, to the best of our knowledge, to examine an ONC model in NSG mice, which are usually used to investigate cancer, not ischemic or inflammatory diseases [ 27 , 28 , 29 ]. We propose that NSG mice might also serve for the study of the latter conditions, as a neuroinflammatory response is relevant in a wide spectrum of ocular diseases, including diabetic retinopathy [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using this model, Khan et al, [ 75 ] have demonstrated that genetic knockdown of lung microenvironment derived E-, L- and P-selectins results in significantly impaired metastatic progression of TNBC. The PuMA has also been used to identify and test novel therapeutic targets in other cancer models that undergo lung metastasis including Ewing sarcoma [ 76 , 77 ], osteosarcoma [ 78 ] and melanoma [ 79 ].…”
Section: Lung Metastasismentioning
confidence: 99%
“…Using this method, we and several other research groups have shown distal metastasis typical for EwS in secondary bone, lungs, and liver. In addition, xenograft murine models were used to harvest organs and characterize ex vivo lung-specific metastasis in EwS ( 127 , 128 ). Further, xenografts have been reported to be used to test and characterize cell lines that may be developed to be chemoresistant ( 129 131 ), radiation-adapted ( 132 ), or designed as organ-specific metastatic cell lines ( 128 ).…”
Section: Animal Modelsmentioning
confidence: 99%